Hubungan Usia dengan Tingkat Kecemasan Pasien pada Saat Pencabutan Gigi di RSUD Nene Mallomo - Utari Zulkaidah; Arsad; Dewi Lidiawati; Indirwan Hasanuddin (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2026)
Based on basic health research data (riskesdas) in 2018 released by the Ministry of Health, it was recorded that 57.6% of the Indonesian population experienced dental and oral health problems. However, only 10.2% of them received treatment from dental medical personnel. Anxiety is a feeling of fear that is not clearly defined which is accompanied by uncertainty, helplessness, isolation, and insecurity In this condition, emotions arise in the absence of a specific object being targeted. Anxiety is generally triggered by the unknown and often accompanies any new experience faced by the individual. The purpose of this study was to determine the relationship between age and anxiety levels at the time of tooth extraction. The design of this study is a type of analytical observational research that adopts a cross-sectional design. The researcher applied the sampling technique with the accidental sampling method. This research method is based on chance, where anyone who unexpectedly encounters a researcher can be sampled, provided that the individual is considered relevant as a data source. Research Results: The results of the chi-square statistical test of the relationship between age and the patient's anxiety level showed a p value of 0.000 because the p value < 0.05 then h0 was rejected and ha was accepted, which means that there is a significant relationship between age and the patient's anxiety level at the time of tooth extraction at RSU Cahaya Medika Makassar. Conclusion The study found a relationship between age and the level of anxiety of patients at the time of tooth extraction with moderate (low) anxiety levels of 11 respondents of 36%, while the level of severe anxiety of 3 respondents was 10% and the level of high anxiety was 53.3% of 16 respondents